A framework on the use of agile methods in logistics startups - Malena Zielske; Tobias Held; Athanasios Kourouklis (Logistics, 2022)
Background: The logistics industry has seen the emergence of many startups in recent years. Many of these logistics startups use new technologies to develop disruptive products, services or platforms that are based on software. This paper presents the results of a Delphi study and a survey that were consolidated in a framework. The purpose is to understand the benefits that logistics startups derive from using agile methods, the difficulties they face in using these methods and the evolution of logistics startups in terms of using agile methods. Methods: A Delphi study with 29 experts and a global survey with 95 participants was conducted to look at the implementation of agile methods. The largest group of participants were members of (top) management, agile coaches and team leaders. Results: The framework consolidates gathered data to demonstrate how logistics startups apply agile methods and practices based on the results of the Delphi study and the survey, and how the usage of agile methods changes over the age of logistics startups. The results indicate that younger logistics startups use agile methods predominantly to design product features and maximise customer value, whereas logistics startups older than five years focus more on the optimisation of internal processes. Conclusions: The value of the present study lies in its contribution to the hitherto hardly examined research field of agility in logistics startups and the notable views of the experienced participants.
Keywords: 650; agile methods; Delphi study; framework; logistics; startups; survey